Structural evolution and strain generation of derived-Cu catalysts during CO2 electroreduction - Qiong Lei; Liang Huang; Jun Yin; Bambar Davaasuren; Youyou Yuan; Xinglong Dong; Zhi-Peng Wu; Xiaoqian Wang; Ke Xin Yao; Xu Lu; Yu Han (Nature Communications, 2022)
Copper catalysts derived from oxidized precursors typically exhibit high selectivity for CO2 electroreduction to multicarbon products, yet the influencing factors that control the selectivity need further investigation. Here, the authors reveal that the high selectivity stems from small grain size and lattice strain due to in situ reduction of precursors.